Analisis Functional Theory dan Personal Qualities dalam Debat Pilkada Kalimantan Selatan 2024 - Shanti, Ni Ketut Rahma Pratiwi; Fuady, Ikhsan; Wibowo, Kunto Adi (Department of Political Science, Universitas Islam Negeri Alauddin Makassar, 2025)
This study aims to analyze political communication strategies in the 2024 South Kalimantan regional election debate using Benoit’s Functional Theory and Personal Qualities approach. The study employs content analysis with a quantitative approach, examining candidates’ verbal statements in the debate accessed via YouTube. The total units of analysis are 800. The findings show significant differences between the two candidates, as evidenced by the chi-square test results (p < 0.001) in the use of functions (acclaim, attack, defense) and personal qualities (leadership ability and values/principles). Candidate 1 is dominant in using defense and highlighting leadership ability, while Candidate 2 is dominant in using acclaim and attack, emphasizing values/principles. This study complements previous research and contributes new insights to the development of political debate theory, particularly Functional Theory and Personal Qualities.